Long-Term Effects of Ivabradine on Cardiac Vagal Parasympathetic Function in Normal Rats - Scridon, Alina; Halaţiu, Vasile Bogdan; Balan, Alkora Ioana; Cozac, Dan Alexandru; Moldovan, Valeriu; Bănescu, Claudia; Perian, Marcel; Şerban, Răzvan Constantin (Frontiers in Pharmacology, 2021)
Background: The complex interactions that exist between the pacemaker current, If, and the parasympathetic nervous system could significantly influence the course of patients undergoing chronic therapy with the If blocker ivabradine. We thus aimed to assess the effects of chronic ivabradine therapy on autonomic modulation and on the cardiovascular response to in situ and in vitro parasympathetic stimulation. The right atrial expression of HCN genes, encoding proteins for If, was also evaluated. Methods: Sympathetic and parasympathetic heart rate variability parameters and right atrial HCN(1-4) RNA levels were analyzed in 6 Control and 10 ivabradine-treated male Wistar rats (IVA; 3 weeks, 10 mg/kg/day). The heart rate (HR) and systolic blood pressure (SBP) responses to in situ electrical stimulation of the vagus nerve (2–20 Hz) were assessed in 6 additional Control and 10 IVA rats. The spontaneous sinus node discharge rate (SNDR) response to in vitro cholinergic receptors stimulation using carbamylcholine (10−9–10−6 mol/L) was also assessed in these later rats. Results: Ivabradine significantly increased vagal modulation and shifted the sympatho-vagal balance toward vagal dominance. In Control, in situ vagus nerve stimulation induced progressive decrease in both the SBP (p = 0.0001) and the HR (p< 0.0001). Meanwhile, in IVA, vagal stimulation had no effect on the HR (p = 0.16) and induced a significantly lower drop in SBP (p< 0.05). IVA also displayed a significantly lower SNDR drop in response to carbamylcholine (p< 0.01) and significantly higher right atrial HCN4 expression (p = 0.02). Conclusion: Chronic ivabradine administration enhanced vagal modulation in healthy rats. In addition, ivabradine reduced the HR response to direct muscarinic receptors stimulation, canceled the cardioinhibitory response and blunted the hemodynamic response to in situ vagal stimulation. These data bring new insights into the mechanisms of ivabradine-related atrial proarrhythmia and suggest that long-term If blockade may protect against excessive bradycardia induced by acute vagal activation.